Modern minority Asian American literature and everyday life - Lee, Yoon Sun. (New York : Oxford University Press, 2013)
'Modern Minority' presents a fresh examination of canonical and emergent Asian American literature's relationship to the genre of realism, particularly through its preoccupation with everyday life.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: American literature -- Asian American authors -- History and criticism; Realism in literature